Development of Learning Videos on the Atomic Model Concepts Based on Multilevel Representation - Islami, Agustina Amalia; Gunawan, Rony; Erika, Farah; Rahmadani, Agung; Sukemi, Sukemi (Jambura Journal of Educational Chemistry, 2026)
This study was motivated by difficulties in learning complex and abstract concepts in atomic model development, while commonly used learning videos still provide limited representation, reducing students’ ability to connect concepts with real phenomena. This study aims to develop a multilevel representation-based learning video on atomic model development and to examine its validity, practicality, and effectiveness using a research and development approach involving planning, production, and evaluation stages. The subjects in this study included 2 media experts, 2 material experts, 1 chemistry teacher, and 60 tenth-grade students from classes X-5 and X-6 at SMAN 14 Samarinda. Product validity was assessed by experts, practicality was measured through teacher and student questionnaires and activity observations, and effectiveness was analyzed by comparing pretest and posttest results quantitatively. The results show very high validity, with material expert validation reaching 100% and an average media expert score of 99.25%. Teacher practicality was categorized as very practical, with questionnaire and observation scores of 96.67% and 98.33%, while student practicality scores reached 82% and 81.7%, categorized as practical. The effectiveness of the media was demonstrated by an N-gain value of 0.56 (moderate) and an effect size of 4.94 (very strong), supported by positive student responses with ease of understanding scoring of 82.17% and learning interest of 86.33% (excellent category), while learning activity (79.66%) and media practicality and features (79.83%) fell into the good category. These findings confirm that multilevel representation-based learning videos effectively enhance students’ understanding of atomic model development.